Description of the egg cases of Dentiraja polyommata (Rajiformes: Rajidae) and Asymbolus pallidus (Carcharhiniformes: Scyliorhinidae) from Queensland, Australia - Rigby, Cassandra L.; White, William T.; Kyne, Peter M. (Zootaxa, 2017)
Descriptions of the egg cases of Dentiraja polyommata (n = 16) and Asymbolus pallidus (n = 44) are provided from egg cases collected from a commercial trawl fishery off Swain Reefs, central Queensland, Australia. Egg cases of D. polyommata are rectangular, convex and golden-tan in colour and those of A. pallidus elongate, vase-shaped and golden. To determine if a comparative statistical non-metric multi-dimensional scaling approach could identify egg cases of species taken in the same region and fishery, egg cases were compared with the skate D. endeavouri and catsharks A. analis, A. rubiginosus and Figaro boardmani. The statistical approach clearly discriminated the species based on five proportional measurements and identified the morphometrics that separated genera and species. This approach is valuable in a fisheries context for accurate identification of visually similar egg cases that can assist management of oviparous chondrichthyans. A rare incidence of intraspecific chondrichthyan cannibalism was noted for A. pallidus males that consumed egg cases of their own species.